Kinetics Analysis of CO2 Mineral Carbonation Using Byproduct Red Gypsum - Rahmani, O.; Kadkhodaie, Ali; Highfield, J. (2016)
In this study, a simplified model was proposed for CO2 mineral carbonation of red gypsum. The model was based on the PHREEQC-2.18 program, which is used for thermodynamic calculations. Test experiments in an aqueous carbonation reactor were used as reference (Rahmani, O.; Junin, R.; Tyrer, M.; Mohsin, R.Mineral carbonation of red gypsum for CO2 sequestration. Energy Fuels 2014, 28, 5953−5958 and Rahmani, O.; Tyrer, M.; Junin, R.Calcite precipitation from by-product red gypsum in aqueous carbonation process. RSC Adv. 2014, 4, 45548–45557) to verify the model, evaluate the possibility of implementing reactions, and predict the reaction progress over time. At the first step, the model thermodynamic constants and rate expressions were initially determined from experiments in an autoclave mini reactor. These parameters were then included in the model, and their quality was tested by comparing experimental and modeled data in the CO2 mineral carbonation of red gypsum. The evaluated model should prove valuable not only in applications of in situ or ex situ CO2 sequestration but more generally in computational geoscience.